Analisis Pengaruh Faktor Kinerja Terhadap Produktivitas dan Optimasi Dinas Pembekalan TNI AL - Masriansyah, Masriansyah; Purnomo, Untung; Sirait, Binsar Mangaratua (Rekayasa, 2021)
The Navy Debriefing Service is a central implementing agency whose main task is a series of supply chain management, which has several problems related to the uneven competence of Disbekal personnel, limited human resources and lack of creation, innovation, improvisation, as a result of the large number of personnel who have been around for a long time. served in Disbekal. So the purpose of this research is to analyze the influence of competence and the influence of organizational culture partially on the work productivity of Disbekal. As well as analyzing the influence of competence and organizational culture simultaneously on the work productivity of Disbekal. Descriptive verification research method with data analysis techniques using Path Analysis. The number of samples is 88 personnel, with data collection through stratified random sampling. The results showed that there was a significant influence between competence, and organizational culture on the work productivity of the TNI AL debriefing service partially and simultaneously. Where the direct influence of the competence variable is 30.2%, and the organizational culture variable is 18.5%. The total effect is 68.1% overall, while 39.1% is the influence of other factors that were not researched.